Zasady opodatkowania działalności gospodarczej - Małek, Lucyna (My University, 2013)
Praca zawiera omówienie zasad opodatkowania działalności gospodarczej, podstawowych pojęć i zagadnień związanych z działalnością gospodarczą, form jej prowadzenia oraz związane z tym obciążenia. Zawiera także, analizę wpływów podatkowych i budżetowych oraz porównanie podatków w Polsce i krajach Unii Europejskiej.

The main theme of this master's thesis is describing current principles of taxation in Poland in economic activity area. There has also been explained the basic concepts and the vocabulary of this subject and also characterized a different types of economic entities. This work also includes an analysis of tax inflows onto a government budget and also draws comparisons of tax rates between Poland and other European Union countries.
Principles of taxation in Poland in economic activity area
Keywords: podatek; działalność gospodarcza; wpływy budżetowe; zasady opodatkowania; analiza podatków; funkcje podatków; stawki podatku; tax; economic activity; fiscal receipts; principles of taxation; tax analysis; taxes; tax rate